VPN-data center system database / Gan Thai Hwan - Gan , Thai Hwan (2001)
Computer has advanced from high technology equipment that only by large company in the old days to office equipment that is essential in an office. In the world of computer, improvement on service provided and lock out competition is very important The quantity of service, speed of processing, productivity, efficiency and effectiveness is very vital. The purpose of this project is to create a database system to a company that provides services and selling computer product. Beside that, we also provide VPNVirtual Private Network for the company's branch to access and to update the database. This is to provide more security to the data while reducing the traditional cost of Remote Access Server (RAS) connections. Other than that, this project also provides the online purchase and services by only the limited customer. This is easier than the traditional way, which is by telephone or manually. This project is using the VPN server to configure the tunnelling and the encryption and description of the data. The database is created using Microsoft Access and the data entry font to access to the database is created using Visual Basic 6.0.